2004
DOI: 10.12693/aphyspola.106.95
|View full text |Cite
|
Sign up to set email alerts
|

Trapping Center Parameters in TlInS2Layered Crystals by Thermally Stimulated Current Measurements

Abstract: Thermally stimulated current measurements are carried out on TlInS2 layered single crystal with the current flowing perpendicular to the c-axis in the temperature range of 10 to 90 K. The results are analyzed according to various methods, such as curve fitting, heating rate, and initial rise methods, which seem to be in good agreement with each other. Experimental evidence is found for one trapping center in TlInS 2 crystal in the low-temperature region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A phenomenological approach applied for the description of the phase transitions in TlInS2 enabled qualitative agreement with the experimental dependence of thermodynamical functions on temperature to be obtained [3][4][5]. For these materials extensive temperature studies of acoustic [6], electrical [7][8][9][10][11][12], and optical [13][14][15][16] properties were carried out while ellipsometric studies of A III B III C VI (A  Tl, B  (In, Ga), C  (S, Se)) chalcogenides were subject of several publications [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 69%
“…A phenomenological approach applied for the description of the phase transitions in TlInS2 enabled qualitative agreement with the experimental dependence of thermodynamical functions on temperature to be obtained [3][4][5]. For these materials extensive temperature studies of acoustic [6], electrical [7][8][9][10][11][12], and optical [13][14][15][16] properties were carried out while ellipsometric studies of A III B III C VI (A  Tl, B  (In, Ga), C  (S, Se)) chalcogenides were subject of several publications [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 69%
“…Here, and are the area and thickness of the sample, respectively, is the electronic charge, and is the photoconductivity gain, which is equal to the number of electrons passing through the sample for each absorbed photon. The value of is taken unity for the calculation of concentration of the traps [8].…”
Section: Isrn Polymer Sciencementioning
confidence: 99%
“…The shallow levels in the TlInS 2 crystals in the temperature range below 90 K have been studied in Ref. [23]. In this study, the TSC measurements in TlInS 2 crystals over the temperature range of 10-90 K revealed that there was a trap level in the energy gap with activation energy of 12 meV.Özdemir et al [24] have investigated the trap levels in TlInS 2 crystals by TSC spectroscopy in the temperature range of 90-200 K. Analysis of the experimental spectra represented a series of trap levels with energy depths ranging from 150 to 220 meV in the energy gap.…”
Section: Introductionmentioning
confidence: 99%